3′-Sialyllactose protects against osteoarthritic development by facilitating cartilage homeostasis - Jeon, Jimin; Kang, Li Jung; Lee, Kwang Min; Cho, Chanmi; Song, Eun Kyung; Kim, Wook; Park, Tae Joo; Yang, Siyoung (Journal of Cellular and Molecular Medicine, 2018)
3′-Sialyllactose has specific physiological functions in a variety of tissues; however, its effects on osteoarthritic development remain unknown. Here, we demonstrated the function of 3′-sialyllactose on osteoarthritic cartilage destruction. In vitro and ex vivo, biochemical and histological analysis demonstrated that 3′-sialyllactose was sufficient to restore the synthesis of Col2a1 and accumulation of sulphated proteoglycan, a critical factor for cartilage regeneration in osteoarthritic development, and blocked the expression of Mmp3, Mmp13 and Cox2 induced by IL-1β, IL-6, IL-17 and TNF-α, which mediates cartilage degradation. Further, reporter gene assays revealed that the activity of Sox9 as a transcription factor for Col2a1 expression was accelerated by 3′-sialyllactose, whereas the direct binding of NF-κB to the Mmp3, Mmp13 and Cox2 promoters was reduced by 3′-sialyllactose in IL-1β-treated chondrocytes. Additionally, IL-1β induction of Erk phosphorylation and IκB degradation, representing a critical signal pathway for osteoarthritic development, was totally blocked by 3′-sialyllactose in a dose-dependent manner. In vivo, 3′-sialyllactose protected against osteoarthritic cartilage destruction in an osteoarthritis mouse model induced by destabilization of the medial meniscus, as demonstrated by histopathological analysis. Our results strongly suggest that 3′-sialyllactose may ameliorate osteoarthritic cartilage destruction by cartilage regeneration via promoting Col2a1 production and may inhibit cartilage degradation and inflammation by suppressing Mmp3, Mmp13 and Cox2 expression. The effects of 3′-sialyllactose could be attributed in part to its regulation of Sox9 or NF-κB and inhibition of Erk phosphorylation and IκB degradation. Taken together, these effects indicate that 3′-sialyllactose merits consideration as a natural therapeutic agent for protecting against osteoarthritis.
Keywords: Administration, Oral; Animals; Cartilage, Articular; Chondrocytes; Collagen Type II; Cyclooxygenase 2; Cytokines; Disease Models, Animal; Homeostasis; Inflammation Mediators; Interleukin-1beta; MAP Kinase Signaling System; Matrix Metalloproteinase 13; Matrix Metalloproteinase 3; Menisci, Tibial; Mice; NF-kappa B; Oligosaccharides; Osteoarthritis; Proteoglycans; SOX9 Transcription Factor; Sulfates; 3′-sialyllactose; cartilage homeostasis; osteoarthritis